Metaphysical animals how four women brought philosophy back to life - Mac Cumhaill, Clare; Wiseman, Rachael ca. 20./21. Jh (Chatto & Windus, 2022)
"A vibrant portrait of four college friends-Iris Murdoch, Philippa Foot, Elizabeth Anscombe, and Mary Midgley-who formed a new philosophical tradition while Oxford's men were away at war"--
Keywords: Anscombe, G. E. M. -- 1919-2001; Murdoch, Iris -- 1919-1999; Midgley, Mary -- 1919-2018; Foot, Philippa -- 1920-2010; Geschichte 1938-1955; Philosophin; Philosophie; Großbritannien; Women philosophers / England; Murdoch, Iris / Friends and associates; Foot, Philippa / Friends and associates; Anscombe, G. E. M. / (Gertrude Elizabeth Margaret) / Friends and associates; Midgley, Mary / 1919-2018 / Friends and associates; Femmes philosophes / Angleterre; Anscombe, G. E. M. / (Gertrude Elizabeth Margaret); Foot, Philippa; Midgley, Mary / 1919-2018; Murdoch, Iris; Philosophy, British; Women philosophers; Great Britain; 1900-1999; Biography; History; Biographies